2010
DOI: 10.1016/s1734-1140(10)70268-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory plasma cytokines in children and adolescents with migraine headaches

Abstract: Studies have shown fluctuations of cytokine levels in patients with migraine headaches; however, further studies are needed to verify these results. Our previous studies suggest increased levels of pro-inflammatory cytokines, such as IL-1alpha, sTNF-RI and TNF-alpha, in children with migraine headaches. In this study, we analyzed anti-inflammatory cytokines interleukin-4 (IL-4), interleukin-10 (IL-10) and interleukin-13 (IL-13) in plasma from children and adolescents with migraine and tension-type headaches du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
18
0
3
Order By: Relevance
“…Headaches in ZIKV-infected individuals were associated with the presence of increased plasma TNF-α, IL-17A, IL-2, IL-9, IL-12p70, MIP-1α, G-CSF, GM-CSF, and VEGF, as well as significantly higher levels of IL-5, suggesting that these cytokines can play a role in the mechanisms underlying headache. Accordingly, high plasma levels of IL-5 ( 36 ), MIP-1α ( 37 ), and RANTES ( 38 ) have been reported in migraine sufferers, but their mechanistic contributions are yet to be investigated. Studies on inflammatory mediators in the pathophysiology of headache have shown the main action of IL-5 during migraine episodes ( 36 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Headaches in ZIKV-infected individuals were associated with the presence of increased plasma TNF-α, IL-17A, IL-2, IL-9, IL-12p70, MIP-1α, G-CSF, GM-CSF, and VEGF, as well as significantly higher levels of IL-5, suggesting that these cytokines can play a role in the mechanisms underlying headache. Accordingly, high plasma levels of IL-5 ( 36 ), MIP-1α ( 37 ), and RANTES ( 38 ) have been reported in migraine sufferers, but their mechanistic contributions are yet to be investigated. Studies on inflammatory mediators in the pathophysiology of headache have shown the main action of IL-5 during migraine episodes ( 36 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiological theory of brainstem trigeminal nerve/vascular inflammation is recognized by major pathogenesis, and proposes that lack of part of the pain control circuits in the trigeminal nerve vasculature lead trigeminal spinal nerve transmitters to excessively stimulate neurogenic inflammation, and then make the trigeminal nerve stimulation conduct pain to the brain cortex retrogradely and anterogradely [ 9 ]. Recent studies found that a variety of vascular active substances, such as nuclear transcription factors-kappa B, IL-6, IL-10, TNF alpha, and TNF beta factor, play an important role in the neurogenic inflammation mechanism of migraine [ 10 ]. Our previous animal experiments and clinical studies found that 5-HT, NF-kappa B, and intercellular adhesion molecule-1 (ICAM-1) are involved in the pathogenesis of the migraine process [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Однако роль цитокинов в патофизиологии ГБ остается неясной. Так, одни авторы указывают на повышение уровня провоспалительных цитокинов при различных видах ГБ, а другие отмечают отсутствие изменений в их плазменных уровнях [41,42].…”
Section: иммунология гбunclassified
“…Boćkowski и соавт. [41] обнаружили увеличение уровней провоспалительных цитокинов (IL-1, sTNF-RI и TNF-α) у детей, страдающих мигренью и ГБН, а также, что уровень IL-1β у пациентов, страдающих мигренью с аурой, значительно выше, чем при мигрени без ауры. В дальнейшем исследователи проанализировали концентрацию противовоспалительных цитокинов (IL-4, IL-10 и IL-13) в плазме у детей и подростков с мигренью и ГБН во время приступов и в межприступный период.…”
Section: иммунология гбunclassified
See 1 more Smart Citation